Agonist binding and g protein coupling in histamine h2 receptor: A molecular dynamics study - Conrad, Marcus; Söldner, Christian; Miao, Yinglong; Sticht, Heinrich (International Journal of Molecular Sciences, 2020)
The histamine H2 receptor (H2 R) plays an important role in the regulation of gastric acid secretion. Therefore, it is a main drug target for the treatment of gastroesophageal reflux or peptic ulcer disease. However, there is as of yet no 3D-structural information available hampering a mechanistic understanding of H2 R. Therefore, we created a model of the histamine-H2 R-Gs complex based on the structure of the ternary complex of the β2-adrenoceptor and investigated the conformational stability of this active GPCR conformation. Since the physiologically relevant motions with respect to ligand binding and conformational changes of GPCRs can only partly be assessed on the timescale of conventional MD (cMD) simulations, we also applied metadynamics and Gaussian accelerated molecular dynamics (GaMD) simulations. A multiple walker metadynamics simulation in combination with cMD was applied for the determination of the histamine binding mode. The preferential binding pose detected is in good agreement with previous data from site directed mutagenesis and provides a basis for rational ligand design. Inspection of the H2 R-Gs interface reveals a network of polar interactions that may contribute to H2 R coupling selectivity. The cMD and GaMD simulations demonstrate that the active conformation is retained on a µs-timescale in the ternary histamine-H2 R-Gs complex and in a truncated complex that contains only Gs helix α5 instead of the entire G protein. In contrast, histamine alone is unable to stabilize the active conformation, which is in line with previous studies of other GPCRs.
CRIS-Team Scopus Importer:2020-09-18
Keywords: G protein-coupled receptors (GPCRs); G; Gastric acid related diseases; Gaussian accelerated simulations (GaMD); Ligand binding mode; Metadynamics; Molecular dynamics simulations; Receptor–ligand interactions; Ternary complex